2004
DOI: 10.1017/s0001867800012891
|View full text |Cite
|
Sign up to set email alerts
|

On the distribution of the breaking strain of a bundle of brittle elastic fibers

Abstract: The maximum-entropy formalism developed by E. T. Jaynes is applied to the breaking strain of a bundle of fibers of various cross-sectional areas. When the bundle is subjected to a tensile load, and it is assumed that Hooke's law applies up to the breaking strain of the fibers, it is proved that the survival strain distribution for a fiber in the bundle is restricted to a certain class consisting of generalizations of the log-logistic distribution. Since Jaynes's formalism is a generalization of statistical the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 8 publications
0
16
0
2
Order By: Relevance
“…Let A(u) = u α u α +(1−u) α be the cdf of the odd log-logistic uniform (Gleaton and Lynch 2004, 2006 distribution. For β ∈ (0, 1), we have 0 < βA(u) < 1.…”
Section: Linear Representationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Let A(u) = u α u α +(1−u) α be the cdf of the odd log-logistic uniform (Gleaton and Lynch 2004, 2006 distribution. For β ∈ (0, 1), we have 0 < βA(u) < 1.…”
Section: Linear Representationsmentioning
confidence: 99%
“…Recently, Gleaton and Lynch (2004, 2006 defined the cdf of the odd log-logistic family with one extra shape parameter α > 0 by whereḠ(x; ξ ) = 1 − G(x; ξ ). More precisely, they showed the following facts:…”
Section: Introductionmentioning
confidence: 99%
“…The odd log-logistic (OLL) family of distributions was originally developed by Gleaton and Lynch [18,19]; they called this family the generalized log-logistic (GLL) family. They showed that: -the set of GLL transformations form an Abelian group with the binary operation of composition; -the transformation group partitions the set of all lifetime distributions into equivalence classes, so that any two distributions in an equivalence class are related through a GLL transformation; -either every distribution in an equivalence class has a moment generating function, or none does; -every distribution in an equivalence class has the same number of moments; -each equivalence class is linearly ordered according to the transformation parameter, with larger values of this parameter corresponding to smaller dispersion of the distribution about the common class median; and -within an equivalence class, the Kullback-Leibler information is an increasing function of the ratio of the transformation parameters.…”
Section: Introductionmentioning
confidence: 99%
“…As distribuições foram obtidas a partir da família de distribuições odd log-logística de distribuições proposta por (Gleaton e Lynch, 2006). Como distribuição de base são utilizadas as distribuições gama generalizada apresentadas por Stacy (1962) e Stacy e Mihram (1965), respectivamente.…”
Section: Considerações Finaisunclassified
“…• Foram obtidas duas novas distribuições a partir do procedimento de (Gleaton e Lynch, 2006). Estas distribuições apresentam maior flexibilidade na modelagem de dados.…”
Section: Considerações Finaisunclassified